Suicide rates around Chinese and western valentine’s days in Taiwan: The roles of gender and marriage status - Cheng-Fang Yen; Vincent Chin-Hung Chen; Hsing-Ying Ho; Ying-Yeh Chen; Dian-Jeng Li; Ray C. Hsiao; Yi-Lung Chen (PLoS ONE, 2025)
Background The suicide risk on Chinese Valentine’s Day and its potential risk factors have not been examined. This study assessed whether the suicide rates around Chinese and Western Valentine’s Days differed from the rest of the year in Taiwan, and the roles of various genders and marital statuses. Methods This study analyzed daily suicide data from Taiwan’s Cause of Death Statistics between January 2012 and December 2022. We compared the suicide rate of each day in the week before and after Chinese and Western Valentine’s Days with those of the remainder of the year using Quasi-Poisson regression models stratified by gender and marital status. We then performed a moderation analysis to explore whether the effect of Valentine’s Day on suicide differed by gender. Results Married women reported a higher suicide risk on the third day after Chinese Valentine’s Day than married men did. Although a similar trend was observed in Western Valentine’s Day between married women and men, it did not reach statistical significance. Conclusion Suicide rates for certain days in the week before or after Chinese and Western Valentine’s Days were different from other days of the year, and these differences were gender- and marital status-specific.